Occipital Condyles Congenital Dislocation and Condylus Tertius: An Unstable Association Revealing a New Abnormality of the Craniocervical Junction. Issue 17 (1st September 2015) - Lofrese, Giorgio; De Iure F, Federico; Cappuccio, Michele; Amendola, Luca
Abstract : Study Design: A case report. Objective: To describe a unique craniocervical junction anomaly and its implications both on mobility and stability of the skull base. Summary of Background Data: Congenital variations in the craniocervical junction (CVJ) are rare and frequently symptomless. Mild traumas may commonly rouse symptoms which help to unveil such anomalies through radiological investigations. Methods: A 73-year-old woman developed a monoparesis of the right arm after a mild craniofacial trauma. Neurological examination revealed hyper-reflexia in the upper limbs, confirming the strength impairment in the right one. Radiology showed a post-traumatic bulbo-medullary contusion sustained by a unique and unstable association of the first occipital condyles congenital dislocation ever reported with a rare condylus tertius. The patient underwent posterior decompression and occipitocervical screw-rod fixation and fusion. Clinico-radiological follow-up highlighted a gradual recovery of the neurologic impairment and the posterior decompression with resolution of the spinal cord contusion. Results: Although apparently stable the hyperostosis and the irregularly shaped condylar surfaces behind the 3-points mechanism of skull base support played a critical role in determining axial instability. The imbalance due to skull-cervical spine malpositioning may consequently trigger a vicious cycle of development of osteophytes leading to spinal cord narrowing with neurologic decline. A surgical strategy providing for posterior decompression and fixation satisfied the need to solve both bulbo-medullary constriction and skull base instability. Conclusion: Clinical evidences about CVJ anomalies are lacking and symptoms, when present, tend to be vague. Although extremely rare clinicians should be aware of CVJ variations by engaging to improve their knowledge of imaging anatomy, embryology, CVJ basic craniometry and anatomic relationships. Studies on developmental control genes may offer future perspectives of early diagnosis and targeted treatments. Level of Evidence: 4 Abstract : Herein the first case of occipital condyles congenital dislocation associated with a structured tertius condylus unveiled due to the onset of neurological symptoms after a mild craniofacial trauma. The hyperostosis and the irregularly shaped condylar surfaces played a critical role in determining respectively bulbo-medullary constriction and axial instability.